Bridging the Gap: Exploring the Role of Computer Science in Enhancing Interactive and Inclusive Learning Environments - Budi Utami Fahnun; Eel Susilowati; Darmastuti; Hadyan Mardhi Fadlillah; Irawaty (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2023)
This article explores the transformative role of computer science in shaping interactive and inclusive learning environments in the educational sector. With the rapid advancement of technology, computer science has become a pivotal element in redefining educational methodologies, facilitating personalized and accessible learning experiences for a diverse student population. This study employs a mixed-methods approach, integrating quantitative data from educational technology usage surveys with qualitative insights from interviews with educators and students. We examine the implementation of computer science tools such as adaptive learning platforms, virtual and augmented reality, and AI-driven educational software, assessing their impact on student engagement, learning outcomes, and inclusivity. Our findings reveal that these technologies not only enhance interactive learning experiences but also significantly contribute to the inclusivity of education by providing tailored learning paths and overcoming traditional barriers. The study highlights the potential of computer science to democratize education, making it more equitable and accessible to learners with varying needs and backgrounds. Furthermore, we discuss the challenges and opportunities in integrating these technologies into existing educational frameworks, offering recommendations for educators, policymakers, and technology developers. This article contributes to the growing body of research on the intersection of computer science and education, providing insights into the future of learning in an increasingly digital world.